2018
DOI: 10.5194/acp-2018-12
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Global modelling of the total OH reactivity: investigations on the missing OH sink and its atmospheric implications

Abstract: Abstract. The hydroxyl radical (OH) plays a crucial role in the chemistry of the atmosphere as it initiates the removal of most trace gases. A number of field campaigns have observed the presence of a "missing" OH sink in a variety of regions across the planet. Comparison of direct measurements of the OH loss frequency, also known as total OH reactivity (kOH), with the 10 sum of individual known OH sinks (obtained via the simultaneous detection of species such as volatile organic compounds and nitrogen oxides)… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 36 publications
2
19
1
Order By: Relevance
“…However, a φ CH3OH of 17% (corresponding to the yield from the chamber experiments of this study, uncorrected for the trioxide interference, see Supplementary Fig. 17 ) increases the global burden of methanol by 14% from the base case scenario, which is lower than the study of Ferracci et al 20 , which found 36% increment of methanol abundances with φ CH3OH of 20% from the scenario with φ CH3OH of 0%. Under these assumptions methanol production is found to be 54.3 Tg/yr, compared to 116.7 Tg/yr (direct production of 66.1 Tg/yr and indirect production through trioxide formation of 50.6 Tg/yr) estimated for φ CH3OH = 30% by Müller et al 18 .…”
Section: Resultscontrasting
confidence: 75%
See 4 more Smart Citations
“…However, a φ CH3OH of 17% (corresponding to the yield from the chamber experiments of this study, uncorrected for the trioxide interference, see Supplementary Fig. 17 ) increases the global burden of methanol by 14% from the base case scenario, which is lower than the study of Ferracci et al 20 , which found 36% increment of methanol abundances with φ CH3OH of 20% from the scenario with φ CH3OH of 0%. Under these assumptions methanol production is found to be 54.3 Tg/yr, compared to 116.7 Tg/yr (direct production of 66.1 Tg/yr and indirect production through trioxide formation of 50.6 Tg/yr) estimated for φ CH3OH = 30% by Müller et al 18 .…”
Section: Resultscontrasting
confidence: 75%
“…To reconcile modelled and measured methanol abundances, Müller et al 18 utilised a yield of 30% for reaction (2c), the upper limit of their calculated range and also the higher rate coefficient 32 , k = 2.8 × 10 −10 cm 3 molecule −1 s −1 . However, Ferracci et al 20 used k = 1.6 × 10 −10 cm 3 molecule −1 s −1 in their modelling study and found comparatively lower CH 3 OH production (60 Tg/yr) using the yield of 40%, suggesting that a far higher yield would be needed to reconcile models with measurements. The experimental data presented herein demonstrates that the branching fraction at 298 K is instead closer to the calculated value of ~7% producing only 22.4 Tg/yr methanol, which is smaller than required to rationalise atmospheric observations.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations